2001 EUROBAROMETER data on digital divides and ICT-disparities in Eu15. (27th June 2005) - Arend, Michal; Steiner, Pia
Due to the rapid increase in the spread and relevance of modern information and communication technologies, informational inequalities between and within nations have gained growing attention in science and policy. These inequalities are often and synonymously called "digital divides" or "ICT-disparities". This paper sums up the most important empirical findings of the SEAMATE project on some forms and aspects of digital divides and ICT-disparities in Europe. It is based on a disaggregated analysis of 2001 EUROBAROMETER survey data on the access to and usage of ICT in 15 member states of the European Union. The second section is dedicated to the analysis of national and socio-demographic disparities in computer, internet and mobile phone usage. In the third section, we will analyse the home ownership of (or access to) these three information and communication technologies. The final two sections deal solely with computers and investigate the relationship between the domestic ownership (access) and factual usage of computers and the spatial contexts (places) of computer usage.